Quality Assurance in Higher Education in the Context of European Approaches - Marina A. Izmailova; Evgenia Yu. Korneva; Vasily I. Makolov; Tatiana A. Salimova (National Research Mordova State University, 2020)
Introduction. Quality assurance issues are among the priorities in the activities of Russian and European universities. In this regard, the authors of the articles explore various approaches to quality assurance in educational organizations; analyze the results of the study related to the assessment of European procedures, models and mechanisms of quality assurance implemented in Russi an universities. Materials and Methods. At the end of 2019, the authors conducted a survey using the Google Docs service of expert representatives across various types of Russian universities. The study involved 104 experts from 50 regions of Russia. The study was based on an expert online survey and statistical analysis of the results. Results. The results of the survey indicate that in Russian universities the most widespread models are quality assurance based on the requirements of state accreditation and a model based on ESG ENQA standards. Higher education institutions give priority to the development of basic documents to guarantee the quality of education at the institutional level without regulating the non-key aspects of education. In most universities, the responsibility for coordinating activities in the field of quality is assigned to the vice-rector (usually for academic studies). Universities are quite actively conducting surveys of students; it is on this group of interested parties that they emphasize the process of implementing feedback on the quality of education. It is common practice to discuss the results of analysis of surveys of stakeholders at the level of academic councils/senates. The most common quality assurance tools include: interviewing students, employers, teaching staff and employees on the quality of education, monitoring the employment and career growth of graduates, and professional and public accreditation. Most respondents indicated such priority problems as the lack of a unified model for ensuring the quality of education and the shortage of qualified personnel in the field of ensuring the quality of education. Discussion and Conclusion. The results of this study may be useful for further improving the quality of education systems in Russian universities in the context of the Bologna process development.